Mobbing/İş Yerinde Duygusal Taciz: Ulusal ve Uluslararası Boyutu ile Çatışma Yüklü Bir İletişim Biçimi - (:unkn) unknown (My University, 2007)
Özet: Küreselleşmenin yaygınlaştığı ve rekabetin arttığı günümüzde Mobbing/Duygusal Taciz, medyada çok sık ve geniş bir biçimde söz edilen bir olgu haline gelmiştir. Bu olgu ile özellikle iş yerlerinde günlük normal çatışma ve sürtüşmelerin ötesinde, sürekli hale getirilen, düşmanca tacize ve ayrımcılığa hizmet eden bir davranış biçimi ifade edilmektedir. Buna göre mobbing hem mobbing'e uğrayan kişiyi, hem yapılan iş yerini olumsuz yönde etkilemektedir. Bu yüzden demokratik bir toplumda mobbing konusuna sabırla değil, köklü ve etik çözümlerle karşı çıkılmalıdır. Bu makalede, iş yaşamında çalışanların karşılaştıkları kişilik haklarına' saldırı, ayrımcılık gibi çalışanın ruhsal sağlığını doğrudan tehdit eden, dolayısıyla iş huzurunu ve memnuniyetini ortadan kaldırarak iş veriminin düşmesine neden olan, işyerinde "Mobbing/Duygusal Taciz"sorununa dikkat çekilmiş ve özellikle Avrupa Birliği tarafından Mobbing konusunda geliştirilen önleyici ve müdahale edici çözüm önerileri üzerinde durulmuştur.

Abstract: "Mobbing" work place harassment/abuse became one of the most important and discussed terminology and issue in today s globalize and competitive work life. The term mobbing as a destructive behavior pattern is far beyond from daily work place conflicts and can be defined as continued hostile and discriminative mistreatment on a selected victim or victims. Thus, the relevant negative impact of mobbing can have severe effects both on victims and work productivity as well. Therefore it necessitates and seems utmost important to take radical and ethical precautions and measurements against mobbing. This article focuses on mistreatment, work abuse, segration (social isolation) and harassment to personal rights which can generate a serious threat against physical and psychological integrity of the employees and the stereotypical causes of mobbing process comes out as losing job satisfaction and productivity. Also, special emphasize is given on preventive and intervening suggestions for solutions developed by European Union concerning mobbing.
Mobbing/Emotional Abuse at Workplace: National and Internationale Precaution Strategies and Conflict Loaded Communication